Effect analysis of endolymphatic sac surgery on Meniere’s disease based on propensity score matching - Yu SI; Shipei ZHUO; Yan HUANG; Wuhui HE; Jingman DENG; Jintao LOU; Zhigang ZHANG (Zhongguo Linchuang Yixue)
ObjectiveTo analyse the clinical efficiency of endolymphatic sac surgery (ESS) in the management of Meniere’s disease (MD). MethodsA retrospective analysis was conducted on 274 patients with MD who were hospitalized for treatment in Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University from January 2009 to August 2023. All patients received lifestyle management and drug treatment such as diuretics. For those whose conditions were not well controlled 3 to 6 months after the initial treatment, intratympanic glucocorticoid (ITG) or ESS treatment was carried out. Six months after the treatment, the classes of vertigo relief and hearing changes in the patients were evaluated. After adjusting the confounding factors through propensity score matching (PSM), the impact of ESS on the prognosis of MD patients was evaluated. ResultsAmong 274 patients, 194 and 80 patients underwent ITG and ESS, respectively. Eighty patients were enrolled into each group after PSM. Before and after PSM, the rate of patients reaching vertigo relief class A in ESS group was higher than that in the ITG group (P＝0.004); there was no significant difference in hearing preservation between the two groups. Kaplan-Meier curve analysis showed that vertigo relief in the ESS group was better than that in the ITG group (P=0.029); there was no statistically significant difference in hearing preservation between the two groups. ConclusionWhen the initial treatment for patients with MD is ineffective, choosing ESS is more beneficial than ITG for controlling vertigo.